ANALISIS FRAMING DALAM KASUS KONTROVERSI AHOK DI DALAM PILKADA DKI JAKARTA 2017-2022 DI DALAM MEDIA ONLINE KOMPAS.COM DAN REPUBLIKA.CO.ID - Brilliant Indra K; Dra. Taufik Suprihartini, M.Si (Interaksi Online, 2017)
Religion issue used in DKI Jakarta’s election for 2017-2022 involve the candidate of DKI Jakarta Governor No 2, Ahok-Djarot. The controversy attract awareness of online media mass. Media which is writes the controversy have framing from the media politics. This phenomenom become the background from this study. This study aims to describe how the framing is done by media coverage especially from Kompas.com and Republika.co.id. This study using agenda setting theory with the Framing analysis model of Zhondang Pan dan Gerald M Kosicky with usesa constructionist paradigm with qualitative approach. The result showed that Kompas.com is still indicate the presence of media to attempt to approach the objectivity of news reporting while Republika.co.id still indicate to involve their ideology to the news that they have made.